Role of a Clinical Pharmacist in Minimizing Medication Errors through Medication Reconciliation and Patient Counseling in the Department of Gastroenterology - A. Rajani; M. Divya; U. Kruthika; Sudha Sree; Tandava Krishna (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
This chapter highlights about the basic role of pharmacist, is to help in minimizing the errors and to perform medication reconciliation, which was shown to be an important tool in detecting the medication discrepancies and preventing adverse patient outcomes. Medication errors are the most common causes of adverse drug events in patients. A medication error is any preventable event that may cause or lead to inappropriate medication use or patient harm while the medication is in the control of the healthcare professional, patient, or consumer. Such events may be related to healthcare products, professional practice, procedures, and systems, including prescribing, ordering, product labeling, communication, packaging, compounding, dispensing, distribution, administration, monitoring, education, and use. The research was a prospective pharmacist interventional study conducted over a period of 8 months at MNR Hospital, Sangareddy, Telangana state after considering the inclusion and exclusion criteria. The sample size taken was 150 patients and the study population comprise of patients aged 18-80 years, admitted in the hospital during the study period of six months. Medication reconciliation procedures used throughout patient hospitalization, discharge, and follow-up procedures increased the accuracy of medication reconciliation, and the care provided to hospitalized patients made the transition to ambulatory settings safer. Out of 150 patients there were 98 (65.33%) male patients and 52 (34.67%) female patients. Patients between 18 and 30 years of age were 29(19.33%), between the age 30 and 50 years were 71 (47.33%) and above 50 were 50(33.33%). Pancreatitis was most prevalent with 21% of total prevalence, followed by CLD and cholelithiasis with 17%, then IBD 16%, PUD and Gastritis 5%, GERD 4% and other diseases 15%. The primary responsibilities of a pharmacist are to do medication reconciliation and to assist in decreasing errors. In order to improve patient safety and behavior changes for a better outcome, pharmacists enlighten patients about the disease and the medications they are taking. It is revealed that the discrepancies were checked and reconciled by which the patient’s quality of life was improved and the discrepancies were reduced. As most of discrepancies were accepted by the physician, it helped to resolve the errors.